(untitled) (Damascus University Journal of agriculture sciences, 2021)
Abstract In this study, Compost Technology was used for organic fertilizer production from pruning residues of Peaches and Apples trees at Messelon area in Damascus countryside at 2015. Three types of compost were produced during five months, they were (peaches pruning residues+ cow manure) compost, (Apple pruning residues+ Cow manure) compost and (Peaches and Apples pruning residues + Cow manure) compost. The results of the analysis of types of compost during different periods of decomposition showed a significant increase in pH value, electrical conductivity, total nitrogen and total phosphorus .The pH at beginning of decomposition were 6.1 for(peaches pruning residues+ cow manure) compost ,6.1for (Apple pruning residues+ Cow manure) compost and 5.9 for (Peaches and Apples pruning residues + Cow manure) compost ,and the pH increased for all three compost at end of decomposition to take 7.55 value .The results also showed a significant decrease in total carbon value and C / N ratio between the beginning of decomposition and the end of decomposition process of the three types of compost. The ratio of C / N at the beginning of the decomposition in the three composts were (34.2, 35.9, 35.4) in the previous order and decreased to register (21.5, 20.3, 22.3) in the three composts.